Use of a Heimlich flutter valve for pneumothorax in cystic fibrosis. Issue 11 (November 1994) - Edenborough, F P; Hussain, I; Stableforth, D E
Abstract : The use of a Heimlich flutter valve in an adult patient with cystic fibrosis with hypercapnic respiratory failure which allowed resolution of a persisting pneumothorax after failure of conventional tube drainage is reported. The patient was managed at home and avoided surgical pleurodesis which could have jeopardised transplantation at a later date.